Social information use about novel aposematic prey depends on the intensity of the observed cue. (3rd June 2022) - Mulà, Clelia; Thorogood, Rose; Hämäläinen, Liisa
Abstract: Animals gather social information by observing the behavior of others, but how the intensity of observed cues influences decision-making is rarely investigated. This is crucial for understanding how social information influences ecological and evolutionary dynamics. For example, observing a predator's distaste of unpalatable prey can reduce predation by naïve birds, and help explain the evolution and maintenance of aposematic warning signals. However, previous studies have only used demonstrators that responded vigorously, showing intense beak-wiping after tasting prey. Therefore, here we conducted an experiment with blue tits ( Cyanistes caeruleus ) informed by variation in predator responses. First, we found that the response to unpalatable food varies greatly, with only few individuals performing intensive beak-wiping. We then tested how the intensity of beak-wiping influences observers' foraging choices using video-playback of a conspecific tasting a novel conspicuous prey item. Observers were provided social information from 1) no distaste response, 2) a weak distaste response, or 3) a strong distaste response, and were then allowed to forage on evolutionarily novel (artificial) prey. Consistent with previous studies, we found that birds consumed fewer aposematic prey after seeing a strong distaste response, however, a weak response did not influence foraging choices. Our results suggest that while beak-wiping is a salient cue, its information content may vary with cue intensity. Furthermore, the number of potential demonstrators in the predator population might be lower than previously thought, although determining how this influences social transmission of avoidance in the wild will require uncovering the effects of intermediate cue salience. Abstract : Predators can learn to avoid toxic prey by observing strong distaste responses of others. We show that the intensity of responses varies among blue tits. Weaker distaste responses were found to be more common, but in contrast to strong responses, they did not elicit prey avoidance in observing birds. This demonstrates that predators pay attention to the intensity of cues, and this can influence how social information about prey defences spreads in the predator population.